STUDENTS' PERCEPTION OF THE INFLUENCE OF THE LEARNING ENVIRONMENT ON ARABIC LANGUAGE LEARNING MOTIVATION: Persepsi Siswa Terhadap Pengaruh Lingkungan Belajar Pada Motivasi Pembelajaran Bahasa Arab - Siska Qurrota A'yun; Rizki Kurniati; Tulus Musthofa; Nasiruddin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The learning environment plays an important role in supporting students' motivation in learning Arabic. This article aims to analyze students' perceptions of the influence of the learning environment on their motivation in understanding and mastering Arabic. This study uses a qualitative descriptive approach with a literature study method, referring to various related literature sources. The results of the study indicate that: 1) Students' perceptions of the learning environment are influenced by various factors, including physical conditions, social support, and additional educational programs. To create optimal Arabic learning motivation, continuous efforts are needed to improve the quality of the learning environment both in terms of physical aspects and social interactions. This is important to ensure the success of the learning process and the achievement of students' academic results to the maximum. 2) A well-designed learning environment, supported by intrinsic and extrinsic motivation, and appropriate teaching methods, can create an effective and enjoyable Arabic learning process. It is important to continue to reduce psychological barriers, such as anxiety, and increase support from teachers, technology, and the social environment so that Arabic learning can provide optimal results for students.